Larval collectors network documents the spread of the invasive bivalve Pinctada radiata in the Mediterranean Sea - Júlia García-Colomé; Iris E. Hendriks; Isabel Abel-Abellán; Giorgio Aglieri; Peru Agueda; Natalia Aisa-Bravo; Elvira Álvarez; María P. Andrada-Nicolás; Irene Antón-Linares; Elisa Arroyo-Martínez; Carolina Audisio-Pacheco; Tatjana Bakran-Petricioli; et al. (Marine Environmental Research, 2026)

Population density and health condition of Cladocora caespitosa in the shallow zone of the Amvrakikos Gulf (Ionian Sea - Western Greece) - ELENI GAVRIEL; PAVLOS AVRAMIDIS; CONSTANTIN KOUTSIKOPOULOS; ALEXIS RAMFOS (Mediterranean Marine Science, 2026)
The Mediterranean coral Cladocora caespitosa is a key species in temperate marine ecosystems, contributing to reef-building processes. However, it faces increasing threats from climate change, pollution, and human activities, in shallow coastal areas in particular This study presents a baseline monitoring project implemented in the Amvrakikos Gulf, Greece, in order to assess the distribution, health, and environmental drivers of C. caespitosa. A total of 26 sampling sites were surveyed across different depth zones and substrate types. Data collection included photographic documentation, in-situ morphometric measurements, and qualitative assessment of colonies at different substrate types and depths. The results show that the colonies on rocky substrates were significantly larger (118.2 ± 53.0 mm) than those on mixed rocky-sandy substrates (67.7 ± 44.8 mm). The average colony density across sites was 0.217 colonies/m², while only 12.5% of colonies were classified as fully healthy, with 56.05% exhibiting partial mortality. As expected, substrate type and depth were identified as key drivers of coral health and morphology. These findings provide useful baseline insights for conservation and management strategies, particularly for semi-enclosed Mediterranean basins vulnerable to climate change.

Large-scale analysis of environmental and ecological impacts of marine finfish aquaculture in the Aegean and Ionian Sea (Eastern Mediterranean) - Sarah Faulwetter; Alexis Ramfos; Pavlos Avramidis (Science of The Total Environment, 2025)

Fan Mussel (Pinna nobilis L.) Spat Collection, Monitoring of Early Growth and Conservation Implications by Deploying Conventional Aquaculture Methodology - John A. Theodorou; Efthimios Spinos; Alexis Ramfos; Ioannis E. Tsamadias; Vlasoula Bekiari; Maria Kamilari; Maria-Myrto Ntouni; Dimitrios Tsotsios; Konstantinos Feidantsis; Athanasios Lattos; Ioannis A. Giantsis; Basile Michaelidis (Journal of Marine Science and Engineering, 2024)
Pinna nobilis, endemic to the Mediterranean Sea, has been experiencing a gradual population decline over recent decades due to anthropogenic pressures on its ecosystems. However, since 2016, its populations have suffered significant reductions because of pathological issues affecting the species across all its habitats. Aquaculture techniques to support the limited natural recruitment P. nobilis efforts is examined. Artificial substrates for larval attachments in aquaculture infrastructures promote the survival of the juveniles that is further enhanced through protected pre-growing “nursery” farming conditions. Specific spat collectors were placed in 2 cage-fish farms in SW Amvrakikos Gulf. The harvested spats from were transferred to pre-grow in trays hanged on a long line farm mussel that is acting as a protected “nursery”, avoiding predation and any human accidentally disturbance. The survival and growth of 12 juveniles P. nobilis spat (shell length 38.1 ± 9.2 mm) in captivity (31 October 2023–15 March2023) was investigated. Out of the 12 individuals collected, 3 were examined for the presence of pathogens; only 7 survived, exhibiting enhanced growth (shell length 54.3 ± 11.6 mm) after 134 days in the nursery. The results highlight the significant role of aquaculture techniques in efforts to conserve a threatened species as well as the need for the creation of a protocol to ensure the conservation of P. nobilis.

Status, distribution, and threats of the last surviving fan mussel populations in Greece - ORESTIS PAPADAKIS; IOANNIS MAMOUTOS; ALEXIS RAMFOS; GAETANO CATANESE; EVANGELOS PAPADIMITRIOU; JOHN THEODOROU A.; COSTAS BATARGIAS; CHARIKLEIA PAPAIOANNOU; MARIA KAMILARI; ELINA TRAGOU; VASSILIS ZERVAKIS; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2023)
Since the first confirmed records of mass mortality events (MME) in the Aegean Sea in 2018, Pinna nobilis populations in Greek seas have been decimated. To bolster recovery efforts, this study aimed to assess the status of fan mussel populations in the Aegean and Ionian seas and investigate potential recolonization through natural recruitment. From May 2022 to May 2023, 163 independent underwater visual surveys were conducted across various locations and depths along the Greek coastline. A total of 4348 P. nobilis individuals was recorded, of which 87.3% were found dead and 12.7% were alive. The sole surviving fan mussel populations were located in the semi-enclosed gulfs of Amvrakikos in the Ionian Sea and of Kalloni in the Aegean Sea, with estimated recent mortality rates (excluding potential poaching) of 7.7% and 6.3%, respectively. To track potential new recruitment, a network of larvae collectors was deployed in multiple locations. Additionally, an ocean circulation model (OCM) was developed to predict the export and fate of larvae from the surviving populations in the Marmara Sea towards the Aegean Sea. Beyond the MME, this study identified several other threats, which significantly endanger fan mussel survival. The findings of this study underscore the urgent need to implement protection measures and restoration actions to enhance the chances of P. nobilis survival and recovery in the Greek seas.

Marinomyxa marina presence in a Halophila stipulacea meadow near a fish farm in south Evoikos Gulf (Greece) - Nefeli Zervou; Varvara Podia; Sarah Faulwetter; Alexis Ramfos; Savvas Genitsaris; Kosmas Haralampidis; Ioannis-Dimosthenis S. Adamakis (Aquatic Botany, 2023)

Monitoring the Kotychi Lagoon in Western Peloponnese, Greece, Using Remote Sensing Techniques and Environmental Assessment - Dionysios N. Apostolopoulos; Dionysios Giannikopoulos; Alexis Ramfos; Sara Faulwetter; Dionisios Panagiotaras; Konstantinos G. Nikolakopoulos; Pavlos Avramidis (Journal of Marine Science and Engineering, 2023)
The Kotychi Lagoon (western Peloponnese, Greece), together with other coastal wetlands such as Pappas, Prokopos and Lamia, is part of the wider area of the Strofylia Wetlands National Park and Protected Areas of Western Peloponnese, which has been protected by the Ramsar convention since 1971 and classified as a Natura 2000 area due to its high diversity and ecological value. This study aimed to estimate the water surface evolution of the Kotychi Lagoon using optical remote sensing techniques to record parameters and indices related to the geometrical and landscape orientation features for the 1945–2016 period and to evaluate the ecological and environmental status of the lagoon through in-situ measurement and sample analysis. High-resolution aerial photos at a scale of 1:30,000, orthomosaics, and satellite images were used and linear regression rates (LRR) were calculated to determine the changes. Seasonal sampling of water, sediment, and macrofaunal organisms in the lagoon was performed to monitor environmental and ecological parameters. The results showed that the lagoon’s water surface shrank during the 1945–2016 period, showing different rates in four segments. The shrinkage prevailed in the northeastern and southern parts of the lagoon, with rates of 17.75 and 6.46 m/year, respectively. The ecological status was determined to be poor, although nutrient input seemed to have been moderate over the study period. We conclude that applying remote sensing techniques using a combination of high-resolution images constitutes an effective and accurate method for the spatiotemporal mapping of wetlands. The ecological problems of the Kotychi Lagoon were highlighted and confirmed through complementary in-situ analyses. These problems need to be addressed by the respective managerial bodies in order to restore the lagoon to good ecological status.

Pinna nobilis in the Greek seas (NE Mediterranean): on the brink of extinction? - MARIA ZOTOU; PAVLOS GKRANTOUNIS; ELPIDA KARADIMOU; KONSTANTINOS TSIRINTANIS; MARIA SINI; DIMITRIS POURSANIDIS; MARTA AZZOLIN; THANOS DAILIANIS; ELENI KYTINOU; YIANNIS ISSARIS; VASILIS GERAKARIS; MARIA SALOMIDI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean endemic fan mussel Pinna nobilis is suffering an ongoing basin-scale mass mortality event (MME) since 2016. As most Mediterranean populations have collapsed, the species has been declared as Critically Endangered in the IUCN Red List of threatened species. In an effort to track the progress of the MME and provide updated information on the status of the species in the Greek seas, we compiled data collected through dedicated surveys and opportunistic assessments during 2019 and 2020. A total of 14589 fan mussel individuals, of which 81.1% dead, were recorded in 258 site surveys. Of the remaining 2762 live individuals, 256 were juveniles. Two marine areas which still sustain living populations were identified, namely Kalloni Gulf (Lesvos Island), and Laganas Bay (Zakynthos Island). The inner part of Kalloni Gulf appears to maintain the largest surviving population of the species in the eastern Mediterranean, with an abundance estimate of 684000 individuals (95% confidence interval: 322000-1453000). Solitary, potentially resistant, scattered individuals were recorded in several sites. Other previously abundant populations that had been assessed in the past, specifically those of Lake Vouliagmeni (Korinthiakos Gulf), Souda Bay (Crete) and Gera Gulf (Lesvos Island), and which collectively summed up to ~350,000 individuals, have now been wiped out. Our results document the collapse of most P. nobilis populations throughout the Greek seas. The MME has substantially progressed between early 2019 and mid-2020, as indicated by the increase of mortality at sites consecutively monitored multiple times. This work highlights the urgent need for continuous monitoring of surviving populations and calls for the immediate implementation of an effective protection and management strategy that will ensure the persistence of surviving individuals and the production of resistant offspring.

Food web modelling on the structure and functioning of a Mediterranean lentic system - Dimitrios K. Moutopoulos; Maria Th. Stoumboudi; Alexis Ramfos; Konstantinos Tsagarakis; Konstantinos C. Gritzalis; Olga Petriki; Athina Patsia; Roberta Barbieri; Athanasios Machias; Konstantinos I. Stergiou; Dimitra C. Bobori (Hydrobiologia, 2018)

Contrasting multispecies patterns in larval fish production trace inter-annual variability in oceanographic conditions over the N.E. Aegean Sea continental shelf (Eastern Mediterranean) - Stylianos Somarakis; Alexis Ramfos; Andreas Palialexis; Vasilis D. Valavanis (Hydrobiologia, 2011)

Mesozooplankton community structure in offshore and coastal waters of the Ionian Sea (eastern Mediterranean) during mixed and stratified conditions - Alexis Ramfos; Stamatina Isari; Stylianos Somarakis; Dimitris Georgopoulos; Constantin Koutsikopoulos; Nina Fragopoulu (Marine Biology, 2006)